ЗНАМЕТО НА РЕПУБЛИКА МАКЕДОНИЈА ВО АМБЛЕМИТЕ НА АРМ (1992-2018) / THE FLAG OF THE REPUBLIC OF MACEDONIA ON ARM EMBLEMS (1992–2018) - Trajkov, Trajce (Македонски хералд - Macedonian Herald, 2019)
A chronological and a colorful presentation of those emblems of ARM units and commands used during 1992–2018 which contain the flag of the Republic of Macedonia. Legal norms—regulations governing the subject matter—and on the basis of collections material, a total of 43 different ARM emblems are described and presented. Keeping in mind that independent Macedonia changed its flag twice (1992 and 1995), changes were made to the army emblems in accordance with the emerging reality The first emblem of the ARM from 1992, which represented the then state flag, inherited from Socialist Republic of Macedonia, and is considered a collector’s item since it was in use for only four months; then the first general ARM emblems for formal and official uniforms of 1993; rare emblems of ARM units from the 1990s; the 2005 Engineer Regiment emblems with the Sun of Kutleš; as well as existing emblems of ARM commands and units introduced in 2012. A common unifying thread for all of them is the representation of the flag of the Republic of Macedonia.